Artificial Intelligence and Its Influences on Human Cultural Distortion - Salasiyah, Cut Intan; Fatianda, Septian; Manan, Abdul; Fitri, Hazal (STMIK Indonesia Banda Aceh, 2026)
This research examines how artificial intelligence (AI) can influence and distort human culture. AI is viewed as a technology that enables machines or computer systems to mimic human intellectual abilities. The method used is a qualitative method with a descriptive analytical approach. The data sources are obtained from observations of phenomena and literature reviews. The results of the study indicate that the presence of AI, which has greatly facilitated human life, has an impact on aspects of human culture. This problem occurs when the identity, values, and traditions of a society are changed or weakened by strong external influences. Forms of cultural distortion caused by AI can be observed in phenomena such as information distortion and cultural changes in social media, dependence on AI in cultural thinking, the potential risk of cultural misinterpretation, and the influence of AI on the phenomenon of cultural inequality. However, cultural distortion can be prevented with several important steps such as instilling cultural values ​​from an early age, introducing the history and philosophy of the nation's culture, and increasing cultural literacy.